The Association between Urinary Tissue Inhibitor Metalloproteinase 2 (TIMP-2) and Insulin-like Growth Factor Binding Protein 7 (IGFBP-7) and Renal Recovery in Acute Kidney Injury - Emilia; Zulkhair Ali; Ian Effendi; Novadian; Suprapti; Mediarty; Taufik Indrajaya; Mgs. Irsan Saleh (HM Publisher, 2021)
Background. Acute kidney injury (AKI) is a common and serious medical condition associated with significant increases in morbidity, mortality, cost of care and non recovery of kidney function that leads to progression to chronic kidney disease. Cell cycle arrest is implicated in the pathogenesis and repair process following AKI. The urinary cell-cycle arrest markers tissue inhibitor of metalloproteinase-2 (TIMP-2) and insulin-like growth factor binding protein 7 (IGFBP-7) have been utilized to predict the risk of AKI in many studies from specific population with good performance. However, their use in predicting recovery is still lacking. The aim of this study was to determine the association between two novel AKI biomarkers, urinary TIMP2 and IGFBP7 and renal recovery after 7 days of treatment in AKI patients at Dr. Mohammad Hoesin Hospital Palembang. Method. This was a prospective cohort study conducted in dr. Mohammad Hoesin Hospital Palembang from January 2021 until March 2021. Subjects enrolled in this study were patients whom diagnosed AKI based on KDIGO 2012 criteria. Urine samples were collected upon patients’ enrollment within 24 hours of AKI diagnosis. We utilized Sandwich Enzyme Linked Immunosorbant Assay (ELISA) method to detect urinary TIMP-2 and IGFBP-7 levels. The primary outcome is recovery from AKI after 7 days of treatment. Chi square test is used to analyze the association between urinary TIMP-2 and IGFBP-7 levels and renal recovery. Results. There were 70 subjects, only 22 of them were recovered after 7 days (31%). Median of urinary TIMP-2 and IGFBP-7 was 0,0047(0,0001-0,1439) [(ng/ml)2/1000]. There was significant association between urinary TIMP2 and IGFBP7 and renal recovery (p=0,027; OR 3,19; 95% CI 1,116-9,128). Conclusion. There was significant association between urinary TIMP2 and IGFBP7 and renal recovery in AKI patients.